A case of neuromyotonia and axonal motor neuropathy: A report of a HINT1 mutation in the United States. Issue 6 (December 2015) - Jerath, Nivedita U.; Shy, Michael E.; Grider, Tiffany; Gutmann, Ludwig
ABSTRACT: Introduction: HINT1 mutations cause an autosomal recessive distal hereditary motor axonal neuropathy with neuromyotonia. This is a case report of a HINT1 mutation in the United States. Methods: A 30‐year‐old man of Slovenian heritage and no significant family history presented with scoliosis as a child and later developed neuromyotonia and distal weakness. Electrodiagnostic testing revealed an axonal motor neuropathy and neuromyotonic discharges. Previous diagnostic work‐up, including testing for Cx32, MPZ, PMP‐22, NF‐L, EGR2, CLCN1, DM1, DM2, SMN exon 7/8, emerin, LMNA, MPK, SCNA4, acid maltase gene, paraneoplastic disorder, and a sural nerve biopsy, was negative. Results: Genetic testing for a HINT1 mutation was performed and revealed a homozygous mutation at p.Arg37Pro. Conclusion: This entity should be distinguished clinically and genetically from myotonic dystrophy and channelopathies with the clinical features of neuromyotonia and an axonal neuropathy. This case illustrates the importance of identifying the correct phenotype to avoid unnecessary and costly evaluations. Muscle Nerve 52 : 1110–1113, 2015